Polyoxometallate composite material as well as preparation method and application thereof
By preparing the polymetallic acid composite ZrW5@PEI, the efficient selective separation and purification of cytochrome c is achieved by using electrostatic interaction, solving the problem of difficult isolation of cytochrome c in complex biological samples, and supporting the development of disease detection and clinical targeted drugs.
Patent Information
- Application Number
- CN202510392591.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-07-04
AI Technical Summary
The prior art is difficult to efficiently isolate and purify cytochrome c from complex biological samples, affecting disease detection and the development of clinically targeted drugs.
By preparing the polymetal oxidate composite material ZrW5@PEI, the electrostatic interaction between molecules is used to achieve selective adsorption and purification of cytochrome c. The polymetal oxidate ZrW5@PEI is used as the adsorbent, and cytochrome c is isolated from the pig heart supernatant by combining solid phase extraction and elution technology.
Efficient and selective isolation and purification of cytochrome c was achieved, showing an adsorption efficiency of 94% and a maximum adsorption capacity of 166.70 mg·g-1, supporting disease detection and the development of clinical targeted drugs.
Smart Images

Figure CN120242981A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of protein separation and purification and materials, and more specifically, to a polyoxometalate composite material, a preparation method thereof, and an application thereof, especially the application of the polyoxometalate composite material in protein separation and purification. Background Art
[0002] Cytochromes are widely present in animals, plants, and microorganisms. According to the structure of the cytochrome cofactor (iron porphyrin or heme), they are divided into cytochromes a, b, c, etc. Among them, the one containing the heme c structure is cytochrome c. Cytochrome c (Cyt-c) is a metalloprotein containing a porphyrin ring cofactor located on the inner mitochondrial membrane of non-apoptotic cells. It is an electron transfer protein that mainly conducts electron transfer through Fe in its inner porphyrin ring cofactor. It is an important part of the mitochondrial electron transfer chain and has important physiological functions in cell respiration. Cytochrome c is mainly used clinically for the emergency treatment of tissue hypoxia and is involved in various diseases including the nervous and circulatory systems. Moreover, studies have shown that Cyt-c is closely related to the occurrence, development, and treatment resistance of tumors. For example, a study on NSCLC showed that detecting the serum Cyt-c level helps to indicate the severity of the disease at the time of diagnosis and can also be used as a potential prognostic marker for NSCLC patients. In addition, animal experiments clearly showed that Cyt-c nanoparticles actively targeting NSCLC can inhibit tumor growth. And, as a substance existing in cells themselves, Cyt-c is not likely to cause adverse reactions. However, since free cytochrome c is difficult to enter cells, studying its targeted preparations is the key to exerting the role of cytochrome c.
[0003] In addition, the molecular chain of Cyt-c is composed of 104 amino acids arranged in a specific structure. Among them, histidine at position 18 and methionine at position 80 are respectively connected to the iron porphyrin ring heme by coordination bonds. Such a morphological structure is extremely similar to the catalytic active center of HRP, and studies on the catalytic activity of HRP have pointed out that the change in the hydrophobicity and exposure of its active center is closely related to the improvement of catalytic function. Cyt-c can also act as an antioxidant enzyme in mitochondria to remove superoxides and hydrogen peroxides in mitochondria. Importantly, different from many other antioxidants, Cyt-c continuously undergoes oxidation-reduction processes during cell respiration without being damaged, making it an ideal antioxidant. Therefore, separating and purifying cytochrome c from complex actual biological samples and analyzing its structure and properties have important clinical significance for disease detection and treatment and the development of clinical targeted drugs.
[0004] Polyoxometalates (POMs), also known as polyoxoacids, are metal-oxide cluster-based metal oxides composed of oxygen and metals in the highest oxidation states of Group V and Group VI (such as W, Mo, V, etc.). They have excellent redox properties, large size, high negative charge, nucleophilicity, and thermal stability. Moreover, polyoxometalates generally exhibit a cage-like structure and can combine with inorganic molecules, organic molecules, or ions to form supramolecular compounds. Therefore, they have been widely used in many fields such as catalysis, medicine, electrochemistry, photochromism, magnetism, and medicine, and have attracted the attention of researchers. Summary of the Invention
[0005] In view of the problems existing in the above-mentioned background technology, the present invention provides a polyoxometalate composite material, a preparation method thereof, and an application in protein separation and purification. The present invention realizes the specific separation and purification of high-quality and non-destructive Cyt-c in complex biological samples based on the interaction between POMs and heme. The significance of the present invention lies in preparing POMs composite materials, regulating the functional properties of the materials, realizing the rapid separation and purification of Cyt-c in complex biological samples, and establishing a method for separating and purifying Cyt-c. The present invention can realize the separation and purification of cytochrome c in complex biological samples, providing a theoretical basis and technical support for the detection and treatment of diseases and the development of clinical targeted drugs.
[0006] To achieve the above object, the present invention is realized through the following technical solutions:
[0007] In the first aspect of the present invention, a preparation method of a polyoxometalate composite material is provided, including the following steps:
[0008] S1. Preparation of polyoxometalates, including the following steps:
[0009] a1. Dissolve Na2SO4 in water and adjust the pH to 2 to obtain a Na2SO4 solution; the mass-volume ratio (g / mL) of Na2SO4 to water is 0.142:1;
[0010] a2. Add ZrClO2·8H2O to the Na2SO4 solution. After dissolution, dilute the dissolved solution with deionized water to obtain solution A; the concentration of solution A is 0.005 mol / L;
[0011] a3. Dissolve Na2WO4·2H2O in deionized water, boil it, and immediately cool it in an ice bath after dropwise adding a hydrochloric acid solution under vigorous stirring to obtain a pale yellow solution B; the mass-volume ratio (g / mL) of Na2WO4·2H2O to deionized water is (0.094 - 0.095):1, the concentration of hydrochloric acid is 5 mol / L, and the dropping amount of hydrochloric acid is 22 - 23 wt%;
[0012] a4. Add solution B dropwise to solution A and leave it at room temperature for 3 days to obtain solution C;
[0013] a5. Add tetramethylammonium chloride to solution C, leave it at room temperature for 3 days, filter and take the solid to obtain the polyoxometalate C8H 30 N2O 21 W5Zr, denoted as polyoxometalate ZrW5;
[0014] In step S1, the molar ratio of Na2SO4, ZrClO2·8H2O, Na2WO4·2H2O and tetramethylammonium chloride is (16 - 17):(0.13 - 0.14):(0.6 - 0.7):1;
[0015] S2. Preparation of the composite material, including the following steps:
[0016] b1. Add polyoxometalate ZrW5 to deionized water and stir until it is clear and transparent to obtain solution D; the concentration of solution D is 0.04 - 0.05 mol / L;
[0017] b2. Dropwise add the polyethyleneimine solution to solution D under stirring, stir at room temperature for 7 h, take the solid, wash and dry it to obtain a white solid, denoted as polyoxometalate composite material ZrW5@PEI; the volume ratio of the polyethyleneimine solution to solution D is 1:6.
[0018] Under the preferred scheme, the concentration of the polyethyleneimine solution is 100 mg·mL -1 .
[0019] Under the preferred scheme, in step b2, the solid is washed with deionized water 3 - 5 times and then dried at 60 °C for 24 h to obtain a white solid.
[0020] In the second aspect of the present invention, a polyoxometalate composite material prepared by the above preparation method is provided.
[0021] In the third aspect of the present invention, an application of the above polyoxometalate composite material in protein separation and purification is provided.
[0022] Under the preferred scheme, the application of the above polyoxometalate composite material in protein separation and purification is used for the separation of cytochrome c.
[0023] Under the preferred scheme, the application of the above polyoxometalate composite material in protein separation and purification includes the following steps:
[0024] Dilute the supernatant of pig heart with a pH 10.0 BR buffer solution by 3 times, add 2 mg of the polyoxometalate composite material ZrW5@PEI to the dilution, perform solid-phase extraction for 10 minutes, and use a concentration of 1 mol·L-1 Tris was used as the eluent for cytochrome c to elute cytochrome c on the surface of the polyoxometalate composite material ZrW5@PEI. After 10 minutes of elution, the supernatant was collected to obtain cytochrome c.
[0025] The beneficial effects of the present invention are as follows:
[0026] Compared with the prior art, the present invention prepared a polyoxometalate composite material ZrW5@PEI modified with a polymer material through intermolecular electrostatic interaction, and applied the prepared polyoxometalate composite material ZrW5@PEI to the separation and purification of cytochrome c in porcine hearts; the results showed that under the corresponding conditions, ZrW5@PEI had a selective adsorption performance for cytochrome c. The new method using ZrW5@PEI as an adsorbent has been successfully used for the selective separation of cytochrome c in porcine hearts and shows great potential in the separation and identification of cytochrome c in porcine hearts. Description of the Drawings
[0027] Figure 1 Infrared spectra of ZrW5 and the polyoxometalate composite material ZrW5@PEI prepared in Example 1.
[0028] Figure 2 XRD spectra of ZrW5 and the polyoxometalate composite material ZrW5@PEI prepared in Example 1.
[0029] Figure 3 XPS spectra of ZrW5 and the polyoxometalate composite material ZrW5@PEI prepared in Example 1.
[0030] Figure 4 Scanning electron microscope images of ZrW5 and the polyoxometalate composite material ZrW5@PEI prepared in Example 1.
[0031] Figure 5 Transmission electron microscope images and EDS of ZrW5 and the polyoxometalate composite material ZrW5@PEI prepared in Example 1.
[0032] Figure 6 Effects of pH, salt concentration and adsorption time on the adsorption of cytochrome c; among them, Figure 6 A shows the effect of pH on the adsorption of cytochrome c; Figure 6 B and Figure 6 C show the effects of salt concentration and adsorption time on the adsorption of cytochrome c.
[0033] Figure 7 Adsorption isotherm of cytochrome c; among them, Figure 7 A is the standard solution curve of cytochrome c; Figure 7 B and Figure 7C is the adsorption isotherm of cytochrome c.
[0034] Figure 8 is the SDS-polyacrylamide (SDS-PAGE) gel electrophoresis pattern. Detailed implementation mode
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.
[0036] In the present invention, unless otherwise specified, the scientific and technical terms used herein have the meanings commonly understood by those skilled in the art. The experimental methods in the embodiments are conventional methods unless otherwise specified. For those embodiments not specifying specific conditions, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For reagents or instruments not indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0037] Example 1 Preparation of polyoxometalate composite ZrW 5 @PEI
[0038] A method for preparing a polyoxometalate composite material ZrW5@PEI includes the following steps:
[0039] 1) Preparation of polyoxometalate ZrW5
[0040] Add 500 mL of water to a 1000 mL beaker, add 71 g of Na2SO4 and stir to dissolve. Adjust the solution to pH = 2 with concentrated sulfuric acid or hydrochloric acid. Weigh 1.289 g of ZrClO2·8H2O and dissolve it in the above solution. Then dilute the obtained solution to 800 mL with deionized water to obtain solution A. Weigh 6.60 g of Na2WO4·2H2O and dissolve it in 70 mL of deionized water. Boil and, under vigorous stirring, gradually add 8 mL of 0.04 moL hydrochloric acid solution. Immediately cool it to room temperature in an ice bath to obtain a pale yellow solution, which is solution B. Then gradually add solution B to solution A and let it stand at room temperature for 3 days to obtain solution C. Weigh 3.32 g of tetramethylammonium chloride and add it to solution C. Let it stand at room temperature for 3 days to crystallize the solution. After filtering the solution, obtain polyoxometalate C8H 30 N2O 21 W5Zr, denoted as polyoxometalate ZrW5.
[0041] 2) Preparation of polyoxometalate composite material ZrW5@PEI
[0042] Add 2 g of polyoxometalate ZrW5 to 30 mL of deionized water, stir until clear and transparent to obtain solution D; slowly dropwise add 5 mL of polyethyleneimine (PEI) solution to solution D under stirring conditions, stir at room temperature for 7 h, wash 3 times with deionized water, and dry in an oven at 60 °C for 24 h to obtain a white solid, denoted as polyoxometalate composite ZrW5@PEI.
[0043] The infrared spectroscopy results of ZrW5 and polyoxometalate composite ZrW5@PEI are as Figure 1 shown. As Figure 1 can be seen, in the infrared spectrum of ZrW5, the peaks at 958.07 (W-O t ), 816.77 (W-O e -W) and 619.32 cm -1 are characteristic peaks belonging to the Keggin structure of polyoxometalate. In the infrared spectrum of polyoxometalate composite ZrW5@PEI, the characteristic peaks at 944.92 cm -1 , 813.45 cm -1 and 640.83 cm -1 still belong to the characteristic peaks of the Keggin structure of polyoxometalate. The absorption peak at 3406.02 cm -1 belongs to the stretching vibration peak of N-H, proving that polyethyleneimine has been successfully grafted onto ZrW5.
[0044] The X-ray diffraction patterns of ZrW5 and polyoxometalate composite ZrW5@PEI are as Figure 2 shown. As Figure 2 can be seen, obvious diffraction peaks at 11.51°, 16.30°, 23.1° and 41.43° appear in the XRD pattern of polyoxometalate ZrW5. After modifying with PEI, the above diffraction peaks still appear in the XRD pattern of the polyoxometalate composite. There is no obvious change in the position of the polyoxometalate diffraction peaks before and after modifying with PEI, indicating that the polyoxometalate ZrW5 still maintains a good crystal form after modifying with PEI.
[0045] The XPS curves of ZrW5 and polyoxometalate composite ZrW5@PEI are as Figure 3 shown. As Figure 3 shown in A, in the fitted ZrW5 N1s energy spectrum, only a single C-N peak exists. While in the XPS spectrum of polyoxometalate composite ZrW5@PEI, peaks of elements C, W, Zr, N and O appear ( Figure 3 B). In addition, in the fitted ZrW5@PEI N1s energy spectrum ( Figure 3 C), in addition to the C-N peak, the -NH2 peak on PEI also appears, proving that polyethyleneimine has been successfully grafted onto ZrW5.
[0046] Scanning electron microscope images of the ZrW5 and polyoxometalate composite ZrW5@PEI are as Figure 4 shown. It can be seen from Figure 4 that ZrW5 has a relatively smooth strip structure on its surface. After modifying PEI on its surface, the surface morphology of the polyoxometalate composite ZrW5@PEI has changed significantly, becoming irregular in shape and rough on the surface. Figure 5 The transmission image shown is consistent with the scanning result. The roughness of the polyoxometalate composite ZrW5@PEI after grafting PEI can be seen, indicating that PEI is grafted onto ZrW5 through electrostatic interaction by stirring. The EDS result shows that the polyoxometalate composite ZrW5@PEI is composed of five elements: C, N, O, W, and Zr.
[0047] Example 2 Isolation of cytochrome c (Cyt-c)
[0048] Using the polyoxometalate composite ZrW5@PEI prepared in Example 1 to separate cytochrome c (Cyt-c), the steps are as follows:
[0049] Fresh pig hearts were purchased from the local meat product market, washed with deionized water to remove blood, and then the fibrous connective tissues were crushed with a blender. Weigh 5 g, add 300 mL of deionized water and mix evenly. At the same time, use 1 mol L -1 H2SO4 to adjust the pH of the above mixture to 4, and stir at room temperature for 2 h. Finally, centrifuge the obtained suspension at 8500 r / min for 5 min, discard the precipitate, and collect the supernatant for storage at -20 °C in the refrigerator for later use.
[0050] Dilute the pig heart supernatant 3 times with BR buffer solution with a pH of 10.0. Add 2 mg of the polyoxometalate composite ZrW5@PEI to 1 mL of the diluted solution, perform solid-phase extraction for 10 minutes, and centrifuge at 6000 rpm for 5 min to separate the solid and liquid phases. Use Tris with a concentration of 1 mol·L -1 as the eluent to elute cytochrome c on the surface of the polyoxometalate composite ZrW5@PEI. Oscillate and elute for 10 min, centrifuge at 6000 rpm for 5 min, collect the supernatant, and obtain the cytochrome c eluate; the adsorption efficiency of 2 mg of the polyoxometalate composite ZrW5@PEI for cytochrome c (100 μg·mL -1 ) is 94%, and the maximum adsorption capacity is 166.70 mg·g -1 .
[0051] Example 3 Investigation of polyoxometalate composite ZrW 5 @PEI under different pH conditions for three Effect on protein purification
[0052] Selection of proteins:
[0053] Basic protein cytochrome c (Cyt-c, pI = 10.7), neutral protein hemoglobin (Hb, pI = 7.0), and acidic protein bovine serum albumin (BSA, pI = 4.7).
[0054] Protein adsorption experiment test, including the following steps:
[0055] Weigh 2 mg of the polyoxometalate composite ZrW5@PEI prepared in Example 1 into a 2 mL centrifuge tube, and add 1.0 mL of 100 μg mL -1 model protein solution to it. The pH of the model protein solution is set to 4, 5, 6, 7, 8, 9, 10, and 11 respectively. After mixing, shake and adsorb for 10 min, centrifuge the mixture at 6000 rpm for 5 min, collect the supernatant, and quantitatively analyze the concentration of the residual protein with a U-3900 type ultraviolet-visible spectrophotometer. The detection wavelength of Cyt-c and Hb is 406 nm, and BSA is detected at 595 nm after Coomassie brilliant blue staining. The results are as Figure 6 shown in A. Calculate the corresponding adsorption efficiency (E) according to Equation (1):
[0056]
[0057] where C0 is the concentration of the protein solution before adsorption, and C1 is the concentration of the protein after adsorption.
[0058] Example 4 explores the effect of the polyoxometalate composite ZrW5@PEI on the purification effect of three proteins under different salt concentration conditions
[0059] Selection of proteins:
[0060] Basic protein cytochrome c (Cyt-c, pI = 10.7), neutral protein hemoglobin (Hb, pI = 7.0), and acidic protein bovine serum albumin (BSA, pI = 4.7).
[0061] Prepare a series of model protein solutions with different sodium chloride concentrations (0.1 mol·L -1 ~0.5 mol·L -1 ) at pH = 10.0 respectively. Add 2 mg of the polyoxometalate composite ZrW5@PEI prepared in Example 1 to the protein solution, perform solid-phase extraction for 10 minutes, then centrifuge at 6000 rpm for 5 min, and quantitatively analyze the concentration of the residual protein with a U-3900 type ultraviolet-visible spectrophotometer to investigate the effect of salt concentration on solid-phase extraction. The results are as Figure 6 shown in B.
[0062] Example 5 Investigation of the effect of different adsorption times of polyoxometalate composite ZrW 5 @PEI on the purification efficiency of cytochrome c Effect
[0063] Since it takes a certain amount of time for the solid-phase extraction process to reach equilibrium, in order to allow proteins to adsorb more completely on the surface of the composite material, the effect of adsorption time on the adsorption efficiency of Cyt-c was investigated. At pH = 10.0, 5 min, 10 min, 20 min, 30 min, and 40 min were used as the adsorption times respectively, and 2 mg of the polyoxometalate composite material ZrW5@PEI prepared in Example 1 was used for solid-phase extraction of 1 mL of a 100 μg·mL -1 Cyt-c solution. After adsorption, it was centrifuged at 6000 rpm for 5 min, and the concentration of the residual protein was quantitatively analyzed using a U-3900 type ultraviolet-visible spectrometer. The results are as Figure 6 shown in C.
[0064] The effects of pH, salt concentration, and adsorption time on the adsorption of cytochrome c are as Figure 6 shown. In order to investigate the adsorption behavior of ZrW5@PEI on different proteins, three model proteins were selected for study, an alkaline protein cytochrome c (Cyt-c, pI = 10.7), a neutral protein hemoglobin (Hb, pI = 7.0), and an acidic protein bovine serum albumin (BSA, pI = 4.7). Their adsorption efficiencies in a 0.04 mol·L -1 BR buffer solution (Britton-Robinson) with a pH value of 4.0 - 11.0 are as Figure 6 shown in A. The adsorption efficiency of ZrW5@PEI for Cyt-c is generally above 80%. As the pH increases, the adsorption efficiency gradually increases, and the adsorption trend is relatively stable. Bovine serum albumin BSA still maintains a relatively high adsorption efficiency of about 90% near its isoelectric point, pH 4.0 - 5.0. However, as the pH increases, the adsorption efficiency gradually decreases and basically stops adsorbing near pH 10.0. Hemoglobin Hb also shows the same adsorption effect. When the pH is less than 7.0, the adsorption efficiency remains at a relatively high level. At pH 7.0, the adsorption efficiency has dropped to about 50%. As the pH further increases, the adsorption efficiency continues to decrease, and the adsorption efficiency is the lowest around pH 10.0. At pH 10.0, the adsorption efficiency of ZrW5@PEI for Cyt-c can reach 94%. For the other two proteins, Hb is 4.54% and BSA is 12.64%. In order to obtain high selectivity of ZrW5@PEI for Cyt-c, pH 10.0 was selected as the optimal adsorption condition in this paper. Figure 6Figure B shows the effect of salt concentration on the adsorption of cytochrome c. The adsorption efficiency of cytochrome c by the ZrW5@PEI composite decreases slightly with the increase of NaCl concentration, and the adsorption efficiency is still as high as about 85%. However, the adsorption efficiency of hemoglobin increases gradually with the increase of salt concentration, and the adsorption efficiency of bovine serum albumin (BSA) also reaches about 45%. Therefore, the NaCl concentration of 0 mol·L -1 is the optimal adsorption condition. Figure 6 Figure C shows the effect of adsorption time on the adsorption efficiency of cytochrome c. In order to allow proteins to be adsorbed more completely on the surface of the composite, the effect of adsorption time on the adsorption efficiency of cytochrome c was investigated. It can be seen from the figure that with the increase of adsorption time, the adsorption efficiency of cytochrome c gradually increases. When the adsorption time is 10 min, the adsorption efficiency of cytochrome c reaches the maximum. Further increasing the adsorption time has a limited effect on the improvement of its adsorption efficiency. Therefore, 10 min was used as the adsorption time of cytochrome c in this experiment.
[0065] As Figure 7 shown, Figure A is the standard curve of cytochrome c; Five standard solutions of cytochrome c protein with different concentrations were prepared and the absorbance of the solutions was measured using a U-3900 type ultraviolet-visible spectrometer. The standard curve was plotted as y = 0.00712x + 0.0023, with R 2 = 0.9965; Figure B is the adsorption isotherm curve of cytochrome c. When the concentration of cytochrome c is greater than 400 μg·mL -1 , the unit adsorption capacity of the ZrW5@PEI composite for cytochrome c remains stable, indicating that the adsorption is basically saturated. It can be seen from the figure that the adsorption of cytochrome c on the surface of the ZrW5@PEI composite is monolayer adsorption, and the experimental data conforms to the Langmuir model. As shown in the figure, there is a linear relationship between Ce and Ce Qe -1 , and the linear equation is y = 0.04231 ± 0.00234x, with a correlation coefficient of R 2 = 0.9955. Under the optimal experimental conditions, the theoretical maximum adsorption capacity of the ZrW5@PEI composite for cytochrome c is 166.70 mg·g -1 .
[0066] As Figure 8As shown in the figure, in order to verify the operability of the cytochrome c separation and purification method established in this experiment for actual samples, the prepared ZrW5@PEI polyoxometalate composite material was applied to the separation and purification of cytochrome c in porcine heart supernatant. The results of SDS-PAGE analysis are shown in the figure. Lane 1 is the standard protein molecular weight, and its band range is 10-180KDa; Lane 2 is the diluted porcine heart supernatant diluted 3 times, and there are several main protein bands at 10-180KDa, namely myosin, BSA, actin and Cyt-c; Lane 3 is the protein band of the supernatant after adsorption by ZrW5@PEI. The band of cytochrome c at 12.4kDa basically disappears, while other bands do not change significantly; Lane 4 is the protein band of the eluate after elution with 1mol·L -1 The protein band of the eluate after elution with Tris solution appears at 12.4kDa, which is flush with the band of the standard cytochrome c in Lane 5. The above experimental results show that by controlling the adsorption conditions and using the polyoxometalate composite material ZrW5@PEI as an adsorbent, the controllable separation of cytochrome c in porcine heart supernatant can be achieved.
[0067] Based on the polyoxometalate ZrW5, the present invention uses its surface-active oxygen atoms or electronegativity to perform surface functionalization through certain interactions. The prepared polyoxometalate composite material ZrW5@PEI has high adsorption selectivity for proteins containing heme and can separate and purify high-quality and non-damaged heme-containing proteins from actual biological samples.
[0068] The above is only the preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a polyoxometalate composite material, characterized in that, It includes the following steps: S1. Preparation of polyoxometalate, including the following steps: a1. Dissolve Na2SO4 in water, adjust the pH to 2 to obtain a Na2SO4 solution; the mass-volume ratio (g / mL) of Na2SO4 to water is 0.142:
1. a2. Add ZrClO2·8H2O to the Na2SO4 solution. After dissolution, dilute the dissolved solution with deionized water to obtain solution A; the concentration of solution A is 0.005 mol / L. a3. Dissolve Na2WO4·2H2O in deionized water, boil it, and dropwise add a hydrochloric acid solution under vigorous stirring, then immediately cool it in an ice bath to obtain a pale yellow solution B; the mass-volume ratio (g / mL) of Na2WO4·2H2O to deionized water is (0.094 - 0.095):1, the concentration of hydrochloric acid is 5 mol / L, and the dropping amount of hydrochloric acid is 22 - 23 wt%. a4. Dropwise add solution B to solution A, and let it stand at room temperature for 3 days to obtain solution C. a5. Add tetramethylammonium chloride to solution C, let it stand at room temperature for 3 days, filter and take the solid to obtain the polyoxometalate C8H 30 N2O 21 W5Zr, denoted as polyoxometalate ZrW5; In step S1, the molar ratio of Na2SO4, ZrClO2·8H2O, Na2WO4·2H2O, and tetramethylammonium chloride is (16 - 17):(0.13 - 0.14):(0.6 - 0.7):
1. S2. Preparation of the composite material, including the following steps: b1. Add polyoxometalate ZrW5 to deionized water and stir until it is clear and transparent to obtain solution D; the concentration of solution D is 0.04 - 0.05 mol / L. b2. Dropwise add a polyethyleneimine solution to solution D under stirring, stir at room temperature for 7 h, collect the solid, wash and dry it to obtain a white solid, denoted as polyoxometalate composite material ZrW5@PEI; the volume ratio of the polyethyleneimine solution to solution D is 1:
6.
2. The polyoxometalate composite material according to claim 1 and the preparation method thereof are characterized in that, The concentration of the polyethyleneimine solution is 100 mg·mL -1 .
3. The polyoxometalate composite material according to claim 1 and its preparation method are characterized in that, In step b2, the solid is washed 3 - 5 times with deionized water and then dried at 60 °C for 24 h to obtain a white solid.
4. A polyoxometalate composite material prepared by the preparation method according to any one of claims 1 - 3.
5. An application of the polyoxometalate composite material according to claim 4 in protein separation and purification.
6. Use of the polyoxometalate composite material according to claim 5 in protein separation and purification, characterized in that: For the separation of cytochrome c.
7. Use of the polyoxometalate composite material according to claim 6 in protein separation and purification, characterized in that, It includes the following steps: Dilute the supernatant of porcine heart with a pH 10.0 BR buffer solution by 3 times, add 2 mg of the polyoxometalate composite material ZrW5@PEI to the dilution, perform solid-phase extraction for 10 minutes, and use Tris with a concentration of 1 mol·L -1 as the cytochrome c eluent to elute the cytochrome c on the surface of the polyoxometalate composite material ZrW5@PEI. After eluting for 10 minutes, collect the supernatant to obtain cytochrome c.